Managing The Migration Policies Of Illegal Immigrants In Malaysia Through Policy Transfer Approach - Omar, Nor Sakinah (2023)
Malaysia has always struggled with the issue of illegal immigrants. The fundamental factors behind this population inflow are the country's rapid economic growth and its attractiveness as a destination for foreign workers. This thesis specifically studies Malaysia's policy mechanisms towards illegal immigrants, particularly those who work here. Factors contributing to the influx of illegal immigrants include strong demand for both legal and illegal foreign workers, high costs for the process of employing legal foreign workers, abuse of power among government officials, and Malaysia's unique geographic location. All these elements have been termed "government dilemmas" since they cannot be properly handled due to the limitations and weaknesses of government programmes aimed at this group. This study uncovered mechanisms from other nations using a policy transfer approach. The single border agency and multi-level levy system are still in the planning stages, and the government is taking several steps to thoroughly examine them. The government is making improvements on the existing policies that include the digitalization of migration management, integrating planning with agencies and citizens, strengthening the MOU with the sending nations to achieve a win-win solution, implementing legal reforms for better employment activities, and including NGOs in governing the workers’ rights and welfare. Therefore, it is concluded that the Malaysian government is indeed practicing a policy transfer approach in attempting to curb the issue of illegal immigrants in Malaysia through policy learning and benchmarking.